2014
DOI: 10.1093/mnras/stu063
|View full text |Cite
|
Sign up to set email alerts
|

Extreme infrared variables from UKIDSS – I. A concentration in star-forming regions

Abstract: We present initial results of the first panoramic search for high-amplitude near-infrared variability in the Galactic Plane. We analyse the widely separated two-epoch K-band photometry in the 5th and 7th data releases of the UKIDSS Galactic Plane Survey. We find 45 stars with ∆K > 1 mag, including 2 previously known OH/IR stars and a Nova. Even though the mid-plane is not yet included in the dataset, we find the majority (66%) of our sample to be within known star forming regions (SFRs), with two large concent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 115 publications
5
32
0
Order By: Relevance
“…The distinction between the two classes lies in the magnitude of the outburst, the increase of accretion, the shape of the light curve, and the spectral features observed during outburst. The characteristics of individual objects do not always fully coincide with one of the classes (Herczeg et al 2016), and some authors have suggested that the two classes (or at least, a subset of them) are part of a continuous spectrum of outbursting stars (Contreras Peña et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The distinction between the two classes lies in the magnitude of the outburst, the increase of accretion, the shape of the light curve, and the spectral features observed during outburst. The characteristics of individual objects do not always fully coincide with one of the classes (Herczeg et al 2016), and some authors have suggested that the two classes (or at least, a subset of them) are part of a continuous spectrum of outbursting stars (Contreras Peña et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The longer exposure time for K s aims at increasing the likelihood of detecting young variables since several Galactic studies have shown that variability in this filter is common amongst young stars (e.g. Contreras Peña et al 2014;Lucas et al 2017). It also allows us to better probe high-extinction regions, where young stars are preferentially located.…”
Section: Complementary Datamentioning
confidence: 99%
“…Cody et al 2014) and high amplitude variability is more common (e.g. Contreras Peña et al 2014). These YSOs are also luminous enough to be reliably detected in the individual pawprints.…”
Section: Spitzer Source Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two epochs in the near-IR were obtained during the UKIDDS Galactic Plane Survey (the UGPS) (Contreras Peña et al 2014), but only finding an additional 4 examples arising from embedded sources.…”
Section: Accretion Events In Star Formationmentioning
confidence: 99%